Comparison of Muscle MEPs From Transcranial Magnetic and Electrical Stimulation and Appearance of Reflexes in Horses - Journée, Sanne Lotte; Journée, Henricus Louis; Berends, Hanneke Irene; Reed, Steven Michael; de Bruijn, Cornelis Marinus; Delesalle, Cathérine John Ghislaine (Frontiers in Neuroscience, 2020)
Transcranial electrical (TES) and magnetic stimulation (TMS) are both used for assessment of the motor function of the spinal cord in horses. Muscular motor evoked potentials (mMEP) were compared intra-individually for both techniques in 5 healthy horses. mMEPs were measured twice at increasing stimulation intensity steps, over the extensor carpi radialis (ECR), tibialis cranialis (TC) and caninus muscles. Significance was set at p<0.05. To support the hypothesis that both techniques induce extracranially elicited mMEPs, literature was also reviewed. Results Both techniques show the presence of late mMEPs below transcranial threshold appearing as extracranially elicited startle responses. The occurrence of these late mMEPs is especially important for interpretation of TMS tracings where coil misalignment can have an additional influence. Mean transcranial motor latency times (MLT; synaptic delays included) and conduction velocities (CV) of the ECR and TC were significantly different between both techniques: respectively 4.2 and 5.5ms (MLTTMS--MLTTES), and -7.7 and -7.9 m/s (CVTMS-CVTES). TMS and TES show intensity dependent latency decreases of respectively -2.6 (ECR) and -2.7 ms (TC) /30% magnetic intensity and -2.6 (ECR) and -3.2 (TC) ms/30V. When compared to TMS, TES shows lowest coefficients of variation, highest reproducibility and accuracy for MLTs. This is ascribed to the fact that TES activates a lower number of cascaded interneurons, allows for multipulse stimulation, absence of coil repositioning errors and less sensitivity for varying degrees of background muscle tonus. Real axonal conduction times and conduction velocities are closest approximated by TES. Conclusions Both intracranially and extracranially mMEPs inevitable carry characteristics of brainstem reflexes. To avoid false interpretations, transcranial mMEPs can be identified by a stepwise latency shortening of 15-20 ms when exceeding the transcranial motor threshold at increasing stimulation intensities. A ringblock around the vertex is advised to reduce interference by extracranial mMEPs. mMEPs reflect the functional integrity of the route along brainstem nuclei, extrapyramidal motor tracts, propriospinal neurons and motoneurons. The corticospinal tract appears subordinate in horses. TMS and TES are interchangeable for assessing functional integrity of motor functions of the spinal cord. However, TES reveals significant shorter MLTs, higher conduction velocities and better reproducibility.